2020
DOI: 10.3765/plsa.v5i1.4711
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin has subjectivity-based adjective ordering preferences in the presence of de

Abstract: We investigate adjective ordering preferences in Mandarin, a language that has been claimed to have English-like preferences, but only in the absence of the linking particle de (Sproat & Shih 1991). Extending the experimental methodology of Scontras et al. (2017), we find evidence of robust adjective ordering preferences in Mandarin when de is present. Moreover, the Mandarin preferences are predicted by adjective subjectivity, as in English and other unrelated languages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Empirical investigations of adjective ordering have focused on the cross-linguistic stability of these preferences across a host of unrelated languages (e.g., Dixon, 1982;Hetzron, 1978;Sproat and Shih, 1991). For example, where English speakers prefer 'big blue box' to 'blue big box', Mandarin speakers similarly prefer dà-de lán-de xiāng-zi 'big blue box' to lán-de dà-de xiāng-zi 'blue big box' (Shi and Scontras, 2020). In post-nominal languages, we find the mirror-image of the English pattern, such that adjectives that are preferred closer to the noun in pre-nominal languages are also preferred closer to the noun in post-nominal languages.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Empirical investigations of adjective ordering have focused on the cross-linguistic stability of these preferences across a host of unrelated languages (e.g., Dixon, 1982;Hetzron, 1978;Sproat and Shih, 1991). For example, where English speakers prefer 'big blue box' to 'blue big box', Mandarin speakers similarly prefer dà-de lán-de xiāng-zi 'big blue box' to lán-de dà-de xiāng-zi 'blue big box' (Shi and Scontras, 2020). In post-nominal languages, we find the mirror-image of the English pattern, such that adjectives that are preferred closer to the noun in pre-nominal languages are also preferred closer to the noun in post-nominal languages.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…A number of studies have found support for subjectivity as a predictor of English ordering preferences (behavioral: Scontras et al 2017;corpus: Wulff 2003, Hill 2012, Scontras et al 2017, Hahn et al 2018, Futrell et al 2020. The behavioral methodology from Scontras et al (2017) has been extended to document subjectivity-based ordering preferences in Mandarin (Shi & Scontras 2020), Arabic and Heritage Arabic (Kachakeche & Scontras 2020), Spanish (Scontras et al 2020), and Greek, Hebrew, and Vietnamese (Scontras et al 2021). Relying on English estimates of subjectivity, Trainin & Shetreet (2021) find general support for subjectivity as a predictor of ordering in Hebrew (see also Trainin & Shetreet 2022), although two of the adjective classes they investigated in their behavioral experiments (pattern and texture adjectives) behaved unexpectedly from the perspective of subjectivity alone.…”
Section: Specific Predictorsmentioning
confidence: 99%